Wage adjustment and employment in Europe - Marotzke, Petra; Anderton, Robert; Bairrao, Ana; Berson, Clémence; Tóth, Peter (Nottingham, 2016)
"We explore the impact of wage adjustment on employment with a focus on the role of downward nominal wage rigidities. We use a harmonised survey dataset, which covers 25 European countries in the period 2010-2013. The main advantages of the data are firm-level information on the change in economic conditions and collective pay agreements. Our findings confirm the presence of wage rigidities in Europe: first, collective pay agreements reduce the probability of downward wage adjustment; second, the rise in the probability of downward base wage responses to a decrease in demand is significantly smaller than the rise in the probability of an upward wage response to an increase in demand. Estimation results point to a negative effect of downward wage rigidities on employment at the firm level."